Maternity care provision for women living with female genital mutilation/cutting: A qualitative study from a high asylum‐seeking dispersal context in the UK. (20th February 2023) - Turner, Jessica; Tancred, Tara
Abstract: Objective: To explore the perspectives of midwives and obstetrician/gynaecologists providing maternity care to women living with female genital mutilation/cutting (FGM/C) in a high asylum‐seeker dispersal area in the North West of England. Methods: We carried out a qualitative study in four hospitals providing maternal health services within the North West of England, with the highest population of asylum‐seeking individuals (many from high‐prevalence FGM/C countries) in the UK. Participants included 13 practicing midwives and an obstetrician/gynaecologist. In‐depth interviews were conducted with study participants. Data collection and analysis were carried out concurrently until theoretical saturation was reached. Data were analysed thematically to generate three key overarching themes. Results: There is a disconnect between Home Office dispersal policy and healthcare policy. Participants indicated that there was inconsistent identification or disclosure of FGM/C, constraining appropriate follow‐up and care prior to labour and childbirth. All participants noted existing safeguarding policies and protocols, which were seen by most as being important to protect female dependants, but potentially detrimental to the patient‐provider relationship and to the woman's care. Unique challenges around accessing and maintaining continuity of care for asylum‐seeking women due to dispersal schemes were indicated. All participants highlighted a lack of specialised training for FGM/C to support provision of clinically appropriate and culturally sensitive care. Conclusions: There is a clear need for harmony between health and social policy as well as specialised training that centres holistic wellbeing for the woman living with FGM/C, particularly where there are increased numbers of asylum‐seeking women from high‐prevalence FGM/C countries. Highlights: Training gaps Holistic care need Safeguarding weaknesses Policy limitations